LITERASI KEUANGAN UNTUK OPTIMALISASI PENGELOLAAN KEUANGAN UMKM DI DESA SUMURJOMBLANGBOGO, KECAMATAN BOJONG - Meliza, Meliza; Ilmiani, Amalia; Ulum, Akhmad Samsul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2023)
Understanding of low financial literacy results in Micro, Small and Medium Enterprises (MSMEs) being unable to utilize existing financial products and services. This community service activity aims to increase MSME financial literacy so that they can optimize their financial management. Participants in this PkM activity are MSME actors who are members of a joint business group (KUBE) in Sumurjomblangbogo Village, Bojong District, Pekalongan Regency. The PkM method is carried out in four stages consisting of identification, training in preparing financial reports, socialization on how to apply for a loan, and evaluation. The results of the activity showed that before the socialization about financial literacy was held, only 40% of the participants understood about financial products and services, while only 65% of the total participants understood the importance of financial management. After socialization, 90% of participants understood the importance of financial management, while 84% of participants understood loan products from banks. Keywords: Financial Literacy.